Policy and implementation of gender equality in Indonesian mining companies as an approach to achieve the goals of Indonesian SDGS - Sudaryat Sudaryat; Deviana Yuanitasari; Sonny Dewi Judiasih (Cogent Social Sciences, 2024)
Mining is commonly associated with a male-dominated environment. This stigma has hindered women from working in this industry, despite the constitutional right for both men and women to labor in all major fields allowed by law, public order, and morals. Statistically, there are significantly fewer women working in the mining sector compared to men. Gender equality include job possibilities, work facilities, comfort, and safety in companies. Major mining corporations in Indonesia have established gender equality policies outlined in the Collective Labor Agreement/Company Regulations and company board regulations. However, these policies have not been enforced in small and medium mining firms. All stakeholders are responsible for overseeing the implementation of gender equality. Indonesia’s SDGs aim to achieve gender equality will be easily achieved if there is collaboration among the government, the community and large-scale and small-scale mining companies.